Acaricidal and insecticidal activity of essential oils obtained from the aerial parts of three Mexican Bursera species - Krengel, Felix; Pavela, Roman; Ocampo-Bautista, Fidel; Guevara-Fefer, Patricia (Environmental science and pollution research international, 2023)
In search of new sustainable biopesticides, we determined the phytochemical profiles, acaricidal and insecticidal properties of EOs distilled from the aerial parts of three Mexican Bursera species. Results were obtained by GC-MS analysis and three different bioassays, indicating that the EO of Bursera glabrifolia exhibited high relative abundancies of α-pinene, β-myrcene, and α-phellandrene, as well as promising pesticidal activity against Spodoptera littoralis larvae (LD50,90 = 32.4, 107.2 µg/larva), and Musca domestica (LD50,90 = 23.2, 103.2, and 13.5, 77.4 µg/female or male adult, respectively) and Tetranychus urticae adults (LD50,90 = 7.4, 30.3 µg/cm2). The Bursera lancifolia and Bursera linanoe samples contained mainly D-limonene or linalyl acetate and linalool, respectively, and showed generally less potent pesticidal properties (S. littoralis larva, LD50,90 = 45.4, 154.4 and 52.2, 158.7 µg/larva, respectively; female M. domestica adult, LD50,90 = 69.2, 210.9 and 45.1, 243.8 µg/female adult, respectively; T. urticae adults, LD50,90 = 20.7, 90.5 and 17.5, 71.4 µg/cm2, respectively). However, the EO of B. linanoe exhibited an especially pronounced activity against male M. domestica adults (LD50,90 = 10.6, 77.2 µg/male adult). Our findings prove the pesticidal potential of Mexican Bursera species in the context of integrated pest management (IPM) and highlight the importance of conducting further research to elucidate both the active principles and possibly existing synergistic effects.
Keywords: akaricidy; Male; nadzemní části rostlin; Pesticide; insekticidy; Bursera glabrifolia; mužské pohlaví; Oils, Volatile; Insecticide; Bursera linanoe; larva; Animals; ženské pohlaví; oleje prchavé; zvířata; Bursera lancifolia; Plant Components, Aerial; Insecticides; Bursera; Larva; Female; Essential oil; Acaricide; Integrated pest management (IPM); Acaricides